Letter - Siebert, Hans
1940-01-15 038-0049-002 BASQUE BOYS TRAINING COMMITTEE (AFFILIATED TO THE BASQUE CHILDREN'S COMMITTEE) CHAIRMAN - ROBERT WILLIS (SEC. LONDON TRADES COUNCIL) VICE-CHAIRMAN - MRS. LEAH MANNING SECRETARY - MISS MOLLY GARRETT HON TREASURER - MISS MILDRED HOLLAND 30 ECCLESTON STREET, LONDON, S.W.1. Telephone SLOANE 9866 15th January, 1940 H.V. Tewson, Esq. Transport House Smith Square S.W.1. Dear Mr.Tewson, This is to confirm our telephone conversation about the meeting of representatives of the National Joint Committee, Basque Childrens Committee and Basque Boys Training Committee on Friday, 19th of January, at 11.30 a.m. in this office. Mr. Willis and I, as well as the other members of the Committee, very much hope you will be able to attend, as the subject to be discussed is the older boys and their employment and maintenance. As you know, at the Trades Union Congress our leaflets were circulated and received a favourable reception. And in fact, without the cooperation of the Unions our boys would not have got employment. The good will of Transport House is essential to the functioning of the Basque Boys Training Committee because in the procedure of placing boys we are in effect but agents of the Unions. It is from them that we receive information about vacancies and through them that the boys are referred to the employers while their approval is transmitted to the Local Labour Exchanges. You will appreciate how important a matter is our relations with the Trades Unions when the majority of the children remaining in England are boys of 14 and over who can become partially, and in many cases wholly, self-supporting and thus relieve to great extent the financial responsibility of the Basque Childrens Committee. In addition, and it is the justification of our appeal, these boys are the sons of Trades Unionists who have been victimised by prison or exile. Your presence at the meeting will be especially valuable in view of your position and knowledge of the situation. So we very much hope that you will be able to attend. With many thanks, Yours sincerely, Hans Siebert p.p. Secretary 292/946/38/49(II)